A marr-type regulator directly activates transcription from the Brucella abortus virB promoter by sharing a redundant role with HutC - Sieira, R. (2012)
Type IV secretion systems (T4SS) are multiprotein structures that direct the translocation of specific molecules across the bacterial cell envelope. As in other bacteria, pathogenicity of the genus Brucella essentially depends on the integrity of the T4SS-encoding virB operon, whose expression is regulated by multiple transcription factors belonging to different families. Previously, we identified IHF and HutC, two direct regulators of the virB genes that were isolated from total protein extracts of Brucella. Here, we report the identification of MdrA, a third regulatory element that was isolated using the same screening procedure. This transcription factor, which belongs to the MarR-family of transcriptional regulators, binds at two different sites of the virB promoter and regulates expression in a growth phase-dependent manner. Like other members of the MarR family, specific ligands were able to dissociate MdrA from DNA in vitro. Determination of the MdrA-binding sites by DNase I footprinting and analyses of protein-DNA complexes by electrophoresis mobility shift assays (EMSAs) showed that MdrA competes with IHF and HutC for the binding to the promoter because their target DNA sequences overlap. Unlike IHF, both MdrA and HutC bound to the promoter without inducing bending of DNA. Moreover, the two latter transcription factors activated virB expression to similar extents, and in doing so, they are functionally redundant. Taken together, our results show that MdrA is a regulatory element that directly modulates the activity of the virB promoter and is probably involved in coordinating gene expression in response to specific environmental signals. © 2012, American Society for Microbiology.